Food contamination by packaging : migration of chemicals from food contact materials - Rodríguez Bernaldo de Quirós, Ana; Garcia Ibarra, Verónica; Lestido Cardama, Antia; Sendón, Raquel (De Gruyter, 2019)
The migration of substances from packaging to food is a matter of concern for the food safety authorities, and packaging materials constitute a potential source of contaminants to which the consumer will be exposed to through their diet. A huge variety of substances can be present in packaging materials, which could consequently migrate into food and represent a risk to consumer health. Food Contamination by Packaging provides an overview of the main packaging contaminants including Bisphenol A, melamine, phthalates, alternative plasticisers, photoinitiators, perfluorochemicals, saturated and aromatic hydrocarbons (mineral oil saturated hydrocarbons and mineral oil aromatic hydrocarbons) from mineral oils, other bisphenol-related compounds, nanoparticles, primary aromatic amines and nonintentionally added substances. The analytical techniques used for their determination are reviewed. This book will be of interest to students and researchers in universities and research institutions associated with food packaging and, in general, to the food safety sector